Comparative evaluation of antimicrobial properties and durability to laundering of selected antimicrobial agents on a hospital textile - Sargur Ranganath, Anupama, author; Sarkar, Ajoy K., advisor; Park, Juyeon, committee member; Mallette, Dawn M., committee member (Colorado State University. Libraries, 2011)
The Centers for Disease Control and Prevention, USA estimates that approximately 1.7 million Healthcare Associated Infections (HAIs) and 99,000 associated deaths occur each year on account of infection-causing bacteria. Hence, the control of infections has been identified as the most important target by the United States Department of Health and Human Services. HAIs can be minimized by inhibiting the various routes of transmission of bacteria. Textile substrates have been implicated as one of the vectors of transmission of disease. The spread of infection causing bacteria via textile materials is inhibited by the use of antimicrobial treated textiles. Based on an exhaustive literature review on antimicrobial textiles, it was found that a majority of the research conducted to-date has focused on synthesizing and evaluating uniquely distinct antimicrobial agents on different textile substrates with the main aim of proving their effectiveness against microbes. Very few studies have concentrated on comparing the durability to laundering and antimicrobial efficacy of different agents on a specific substrate against target challenge microorganisms. The present research compared the efficacy and durability to laundering of five antimicrobial agents of distinctive antimicrobial chemistries and modes of action on a polyester-cotton substrate. The antimicrobial agents were based on silver, triclosan, QAC, PHMB and chitosan. The challenge microorganisms were Staphylococcus aureus, a gram positive bacterium and Escherichia coli, a gram negative bacterium. Specimen samples of the polyester-cotton substrate treated with the antimicrobial agents were subjected to a maximum of fifty wash cycles and subsequently evaluated using standard qualitative and quantitative test methods. Scanning Electron Microscopy analysis of the treated and laundered substrates was done to study the difference in topography of the substrates. Statistical analysis for comparing the antimicrobial properties and durability to laundering of the antimicrobial treated fabrics was done using Statistical Analysis System. Qualitative results showed that the triclosan-based antimicrobial agent had superior durability to laundering than the other controlled release antimicrobial agents in this study. SEM analysis of the treated and laundered substrates at ten and fifty wash cycles revealed no visible differences in the topography of the specimen samples. In agreement with qualitative data, quantitative results indicated that triclosan was most effective against both E.coli and S. aureus after fifty wash cycles. Silver, QAC, PHMB and chitosan had higher efficacy against S. aureus than against E.coli. The antimicrobial action of silver, QAC, PHMB and chitosan decreased with increase in number of laundry cycles and the decrease was more pronounced against E.coli.
Keywords: antibacterial; hospital textiles; durability to washing; comparative study; antimicrobial